Obstetric Outcome and its Relationship with Mode of Delivery in Preterm Labour- A Study of 86 Patients in Combined Military Hospital, Dhaka - Asma, Umme Habiba; Juty, Sabikun Nahar; Snigdha, Rezwana Sharmin (Bangladesh Armed Forces Medical Journal, 2024)
Background: Caesarean section in preterm pregnancy may add further pressure to the already existing poorly developed facilities for intensive perinatal care in low resource countries. The objective of the study was to determine the feto-maternal outcome and its relationship with mode of delivery in preterm labour. Methods: This was a descriptive type of cross-sectional study conducted at Department of Obstetrics and Gynecology, Combined Military Hospital (CMH), Dhaka, during March to August 20l8. The study population was total eighty-six patients having 28 to 36 weeks of gestation who were admitted in the above department and were in labour. Data were edited and analyzed by using computer-based software, statistical package for social sciences (SPSS) version 20.0. Results: Majority of the patients belonged to 26-30 years age group and were from low socioeconomic family (71.4 to 72.7) % and had below average nutritional status (88.1 to 93.2) %. The mean gestational age was 31 weeks and 35 weeks. Nulliparous (77.3 to 85.7) % and patients taking irregular antenatal check-up (69.0 to 72.8) % were predominant. About (59.1 to 66.7) % patients had vaginal delivery and (33.3 to 40.9) % patients had undergone caesarean section. Maternal morbidity was more in caesarean section (37.5%) than vaginal delivery (33.3%). Live birth babies were found 100% in caesarean section and 94.4% in vaginal delivery and among them 95.7% were from group I and 97.6% were from group ll. Perinatal mortality was higher in vaginal delivery than caesarean section (7.40% vs 2.7%) and also higher in group I than group ll (8.3% vs 2.3%). But late perinatal complications were more in caesarean section (47.2%) than vaginal delivery (45.1%) baby, and majority (60%) of them were from group l. Conclusion: Preterm pregnancy when leads to an early delivery, brings a grave consequence for both the mother and foetus. After birth, the premature newborn is at risk for complications related to incomplete development of its organ system. Caesarean section delivery in preterm labour improves foetal outcome to some extent, but not significantly, and leads the mother to more maternal morbidity. Perinatal mortality and morbidity is also inversely related to the gestational age at the time of delivery, in preterm labour - more the gestational age, less the perinatal mortality and morbidity. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 43-49